Student’s rating of secondary school physics teachers’ classroom practice: Implications for teaching and learning - Abiodun Adekunle Bada; Loyiso C. Jita (International Journal of Evaluation and Research in Education (IJERE), 2023)
Evaluation in secondary schools has been left in the hands of school management, administrators, and teachers. Little or no attention has been paid to the concerns of students, who happens to be another important stakeholder in the teaching-learning process. Students’ voices regarding teachers’ classroom practice can have great implications for teaching and learning. This study investigated students’ ratings of secondary schools’ physics teachers with particular reference to teachers’ use of instructional material(s), methods, and classroom management. This study adopted the descriptive survey design, which involved 1,256 physics students randomly selected from the three senatorial districts in Ondo, Nigeria. A researcher-designed questionnaire was used to collect data for this research and the data obtained were analyzed using descriptive and inferential statistics. Findings from this study revealed that physics teachers were rated low in their use of instructional materials and instructional methods. However, physics teachers were rated high in the area of classroom management. This study concluded that the use of good instructional materials and methods while still adopting the best classroom management is crucial to the realization of classroom objectives. The paper contributes to the scholarship on how students’ views of their teachers can have great implications for teaching and learning.